Siting of Safe and Secure Truck Parking Areas in Greece and definition of their security level with the use of Multi-Actor Multi-Criteria Analysis (MAMCA). Issue 1 (November 2021) - Kouta, Marina; Nalmpantis, Dimitrios
Abstract: The purpose of this paper is the siting of safe and secure truck parking areas in Greece and the definition of their security level. The increase of road freight transport, and the need for the strengthening of its safety, led to the need for developing a plan for the deployment of safe and secure Heavy Goods Vehicles (HGVs) parking areas. A demand and supply survey led to the development of a plan to address 29.83% of the total demand. Nine (9) stakeholder groups, represented by twelve (12) participants, participated in a Multi-Actor Multi-Criteria Analysis (MAMCA) of the criteria evaluation for choosing the most suitable security level out of the following levels: Bronze, Silver, Gold, and Platinum, for Aigio's Rest Area. The Platinum level was commonly chosen as the most appropriate.